SANITASI PENTING ATASI STUNTING: PEMICUAN PILAR STBM DI RUMAH TANGGA - Irjayanti, Apriyana; Rumbiak, Helmin; Medyati, Novita (Universitas Padjadjaran, 2024)
Stunting is still a nutritional problem currently faced by children under five years of age. This has been proven by the high incidence of stunting in Indonesia, including in Jayapura City. Sanitation plays an important role in reducing stunting because it is closely related to efforts to prevent disease infection. The aim of this community service activity is to educate mothers who have babies/toddlers concerning stunting and implementing good and correct sanitation in the household, and can be one of the steps to support the government's efforts to accelerate stunting reduction. Activities are carried out using lecture and discussion/question and answer methods. The implementation stages include data collection and coordination, activity design, preparation of supporting materials and tools, implementation of triggering and evaluation. The results and achievements of the service activities were assessed as going well. This was demonstrated by the enthusiasm of the participants who attended and participated in the educational implementation until completion. The activity was attended by 30 participants consisting of mothers and other family members who brought their babies and toddlers. The results of the pre-test and post-test evaluation, which was carried out during community service activities carried out at Posyandu Rambay, Kota Baru Village, Abepura Health Center working area, showed that there was an increase in knowledge among participants by 16.6%. It is hoped that participants (mothers and other family members) will be motivated to implement the 5 pillars of Community-Based Total Sanitation (STBM) in their households and this activity can be carried out by health centers routinely in order to support local government programs in order to accelerate the reduction of stunting.Stunting masih merupakan masalah gizi yang dihadapi oleh anak usia di bawah lima tahun. Angka kejadian stunting di Indonesia masih tinggi, salah satunya di Kota Jayapura. Sanitasi berperan penting dalam mengurangi stunting karena berkaitan erat dengan upaya pencegahan infeksi penyakit. Tujuan kegiatan pengabdian kepada masyarakat ini yaitu guna mengedukasi para ibu yang memiliki bayi/balita tentang permasalahan stunting dan penerapan sanitasi di rumah tangga yang baik dan benar, serta dapat menjadi salah satu langkah mendukung upaya pemerintah dalam percepatan penurunan stunting. Kegiatan dilakukan menggunakan metode ceramah dan diskusi/tanya jawab. Tahap pelaksanaan yang dilakukan meliputi pengumpulan data dan koordinasi, perencanaan kegiatan, persiapan materi dan alat penunjang, pelaksanaan pemicuan, dan evaluasi. Hasil dan capaian dari kegiatan pengabdian dinilai berlangsung dengan baik. Hal ini diperlihatkan antusiasme para peserta yang hadir dan mengikuti pelaksanaan edukasi hingga selesai. Kegiatan dihadiri oleh 30 peserta yang terdiri dari ibu-ibu dan anggota keluarga lainnya yang membawa bayi dan balitanya. Hasil evaluasi pre test dan post test pada kegiatan pengabdian kepada masyarakat yang dilaksanakan di Posyandu Rambay, Kelurahan Kota Baru wilayah kerja Puskesmas Abepura, diketahui terdapat peningkatan pengetahuan pada peserta sebesar 16,6%. Diharapkan bagi para peserta (ibu dan anggota keluarga lainnya) terpicu untuk menerapkan 5 pilar Sanitasi Total Berbasis Masyarakat (STBM) di rumah tangganya dan kegiatan ini dapat dilakukan oleh puskesmas secara rutin agar dapat mendukung program pemerintah daerah dalam rangka percepatan penurunan stunting.